HUBUNGAN KONSEP DIRI DENGAN GAYA HIDUP HEDONIS PADA SISWA/I SMA SANTO YOSEF MEDAN TAHUN 2019 - Vina Yolanda Sari Sigalingging; Lindawati Simorangkir; Semirani W (STIKes Santa Elisabeth Medan, 2020)
Introduction : Hedonist lifestyle can bring effects that can damage the next generation of the nation, especially adolescents who are still experiencing an identity crisis in looking for identity so that adolescents have not been able to judge themselves about the strengths and weaknesses of so many adolescents who are easily affected and are mired by unhealthy relationships.Method : This research is correlation analytic research with Cross Sectional approach. The statistical test used is the Spearman Rank. The population in this study were students of SMA Santo Yosef Medan class XI with a total sample of 57 respondents taken by the Quota Sampling technique.Result : The results showed that respondents who lacked self-concept were 27respondents (47%) and moderate hedonic lifestyle as many as 26 respondents (45.6%). Based on the results of the gamma analysis test, a p-value of 0,000 (p <0,005) was obtained so that Ha was accepted or there was a relationship between self-concept and hedonic lifestyles in the students of Santo Yosef Medan High School.Discussion : In this study available that there is a close relationship between self-concept and hedonic style in adolescents, especially students of the Santo Yosef Medan High School. For this reason, it is expected that adolescents will have positive self-concepts to support learning activities and reduce hedonic attitudes in life.